Mediates-A New Approach to Libraries - Adilovna, Qodirova Surayyo; Qizi, Urazbaeva Shakhnoza Komiljon (International Journal on Orange Technologies, 2023)
In the modern world, library buildings are not just old buildings that serve as book shelves or archives, but are now a place for personal development, a world of innovation, a place for seminars, and a place where teams unite and engage. Based on this, the architectural solutions of the building are affected by such demands and proposals and increase its function. In this article, a number of modern architectural solutions needed for library buildings are reviewed and proposed.